SCIENTOMETRIC SKETCH AND ACADEMIC VISIBILITY OF NOBEL LAUREATE SVANTE PÄÄBO (LIS TODAY, 2024)
The swedish scientist Svante Pääbo received his noble prize in Physiology or  Medicine in the year 2022, due to his work for the modern human evolution and the  neandertal genome. The study attempted to ascertain and assess the academic visibility of  nobel laureate Prof. Svante Pääbo from 1974 to 2023. The data was retrieved from the  Google Scholar database. The study makes use of a number of scientometric parameters to  identify Prof. Svante Pääbo's most prolific sources, most referenced works, authorship  patterns, and top publications. Afterwards, the gathered data was processed and examined  using a variety of programmes, including Microsoft Excel, VosViewer, and Publish or Perish.  The study found that during 1974-2023, Prof Pääbo had the most citations (12304) in the  year of 2015. He contributed the most publications (49) in Nature. The research shows that  he collaborated closely with Krause J, Green Re, Kelso J, Prufer, K . His article named "A  global reference for human genetic variation" received the most citations. The collaboration  rate was 0. 86. It was also observed that the most number of publications belongs to the  group of seven authorship (26. 48%).
Keywords: Scientometric; academic visibility; citation metrics